Origin of cooperative transition of antisite-Arsenic defects in Be-doped low-temperature-grown GaAs layers - Mohamed, Mohd Ambri; Lam, Pham Tien; Otsuka, N. (Elsevier, 2013)
A cooperative transition of antisite As (AsGa) defects in Be-doped low-temperature grown GaAs layers was studied by comparing magnetization of samples with different AsGa+ ions concentrations. With the aid of first principle calculations, the origin of cooperative transitions was shown to be due to a lattice strain which results in elastic interactions among AsGa defects. A change in magnetizations is induced by large lattice distortions during transition of AsGa defects from substitutional sites to interstitial sites. The calculation of electron states of an AsGa atom with a shallow acceptor Be atom show that at the transition, an AsGa+ ion is displaced to the interstitial site and becomes a neutral atom, leading to a magnetization annihilation.